Pharmacological interventions for remifentanil-induced hyperalgesia: A systematic review and network meta-analysis of preclinical trials. - Mia E Koponen; Emily Naray; Tim G Hales; Patrice Forget (PLoS ONE, 2024)
Background To improve perioperative pain management, several interventions have been suggested for the prevention of increased pain sensitivity caused by opioids (called opioid-induced hyperalgesia). It is currently unclear which intervention is the most effective or appropriate in preventing opioid-induced hyperalgesia. Remifentanil is the most investigated opioid causing opioid-induced hyperalgesia. Thus, to guide future research, we conducted a systematic review and a network meta-analysis of preclinical trials investigating pharmacological interventions for remifentanil-induced hyperalgesia. Methods To identify relevant articles, electronic database searches were conducted in Embase, PubMed, Web of Science, and Google Scholar. Study characteristics were extracted, and the risk of bias was evaluated. Studies were included in the network meta-analysis if they shared similar characteristics with at least one other study. The interventions were ranked based on P-scores. Results Overall, the 62 eligible trials tested 86 individual interventions and 6 combination interventions. Thirty-five studies eligible in the network meta-analysis formed five groups which were further divided into subgroups based on the quantitative sensory tests used. The best-ranked interventions within the subgroups were Anxa12-26, MRS2179, salicylaldehyde isonicotinoyl hydrazone (SIH), ANA-12, TDZD-8, ketamine, dexmedetomidine, JWH015, and the combination of KN93 and ketamine. Discussion The current literature is too heterogeneous to produce a clear answer on which intervention is the most effective in preventing remifentanil-induced hyperalgesia. Future research in this field should prioritise finding the most effective intervention over testing the efficacy of new options. The results of our work can be used in planning which comparisons should be included in new trials.